The mediating effects of mobile phone use on ADHD and educational outcomes: a two-step Mendelian randomisation study - Lin, Huize; Yuan, Sitong; Yu, Jinna (Frontiers in Psychiatry, 2024)
ObjectiveThis study investigates the potential mediating role of mobile phone screen time in the causal relationships between Attention-deficit/hyperactivity disorder (ADHD) and educational attainment. Our analysis explores both the effect of ADHD on educational outcomes and the reverse, i.e., the influence of educational attainment on ADHD risk.MethodA two-sample Mendelian randomisation (MR) analysis was conducted using genetic instruments from genome-wide association studies (GWAS) of European populations. We employed a two-step MR approach to assess the causal effects between ADHD, mobile phone screen time (both frequency and duration), and educational outcomes, including years of full-time education and college completion. Data from public genome-wide association studies encompassing European populations with sample sizes ranging from 55,374 to 470,941 were utilised.ResultsWe found significant causal associations between childhood ADHD and educational attainment, partially mediated by mobile phone screen time. Childhood ADHD was negatively linked to years of full-time education (IVW: OR = 0.93, 95% CI = 0.90-0.97, p = 0.000) and college completion (IVW: OR = 0.97, 95% CI = 0.95-0.98, p = 0.000). Mobile phone use frequency mediated 19.3% of the effect on full-time education (β = -0.158) and 11.9% on college completion (β = -0.084). The duration of phone use mediated 64.8% of the effect on college completion (β = -0.054). When ADHD was the outcome, phone use duration mediated -22.45% of full-time education effects (β = 0.426) and -19.62% of college completion (β = 0.433).ConclusionDifferent MR models reveal the complex mediation role of mobile phone use frequency and duration between ADHD and educational attainment, varying by educational outcome type. Frequency mediates the link between childhood ADHD and full-time education/college completion, while duration significantly impacts ADHD when higher education is the outcome. The notable mediation effect of duration on ADHD underscores the need for further study into screen time’s influence on ADHD and academic achievement across stages.